Synergistic effects of exosomal crocin or curcumin compounds and HPV L1-E7 polypeptide vaccine construct on tumor eradication in C57BL/6 mouse model. - Elnaz Abbasifarid; Azam Bolhassani; Shiva Irani; Fattah Sotoodehnejadnematalahi (PLoS ONE, 2021)
Cervical cancer is the most common malignant tumor in females worldwide. Human papillomavirus (HPV) infection is associated with the occurrence of cervical cancer. Thus, developing an effective and low-cost vaccine against HPV infection, especially in developing countries is an important issue. In this study, a novel HPV L1-E7 fusion multiepitope construct designed by immunoinformatics tools was expressed in bacterial system. HEK-293T cells-derived exosomes were generated and characterized to use as a carrier for crocin and curcumin compounds. The exosomes loaded with crocin and curcumin compounds as a chemotherapeutic agent (ExoCrocin and ExoCurcumin) were used along with the L1-E7 polypeptide for evaluation of immunological and anti-tumor effects in C57BL/6 mouse model. In vitro studies showed that ExoCrocin and ExoCurcumin were not cytotoxic at a certain dose, and they could enter tumor cells. In vivo studies indicated that combination of the L1-E7 polypeptide with ExoCrocin or ExoCurcumin could produce a significant level of immunity directed toward Th1 response and CTL activity. These regimens showed the protective and therapeutic effects against tumor cells (the percentage of tumor-free mice: ~100%). In addition, both ExoCrocin and ExoCurcumin represented similar immunological and anti-tumor effects. Generally, the use of exosomal crocin or curcumin forms along with the L1-E7 polypeptide could significantly induce T-cell immune responses and eradicate tumor cells.